Resepsi Surah al-Takāṡur dalam Tradisi Marzoah di Pemakaman Islam Kota Medan: Kajian Living Qur’an atas Praktik Memorialisasi Kematian - Muhammad Nur Fadli; Jufri Naldo; Muhammad Akbar Rosyidi Datmi (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The practice of reciting Surah al-Takāṡur in the marzoah tradition in Islamic cemeteries in Medan City represents a form of Qur’an reception that lives within the socio-religious space while simultaneously emphasizing the urgency of a living Qur’an approach to understanding the dynamic relationship between the sacred text and death-ritual practices. The study focuses on analyzing the pattern of community reception, the construction of meaning attached to Surah al-Takāṡur, and the relationship between the text and death-memorialization practices in the local context. A qualitative approach based on the living Qur’an is used, with data collected through participatory observation, in-depth interviews, and documentation, and analyzed using a thematic-interpretive framework to uncover layers of symbolic and functional meaning. The findings show variations in reception patterns that include performative, spiritual, and communal dimensions; Surah al-Takāṡur is understood as an eschatological reminder, an instrument for reflection on mortality, and a medium for strengthening social solidarity in death rituals. The construction of meaning develops through the interaction between normative teachings, local traditions, and the collective experiences of the congregation, resulting in an integration between textual messages and social practices. The relationship between text and practice demonstrates an adaptive negotiation of meaning, where Qur’anic recitation is not merely a symbolic ritual but a means of internalizing values ​​and shaping the community’s religious identity. The implications of this study enrich the theoretical framework of the living Qur’an and provide an empirical contribution to understanding the contextual and meaningful layers of Muslim religious practice.